PENGGUNAAN MEDIA LAGU DALAM PEMBELAJARAN SEBAGAI UPAYA MENINGKATKAN MOTIVASI BELAJAR SISWA TERHADAP MATA PELAJARAN IPAS - Wiratha, Oktaviana Astuti (PT. Media Akademik Publisher, 2024)
This Best Practice writing aims to describe the use of song media to improve students' understanding of the material taught by the teacher. The subjects of this Best Practice writing were 25 students in class IV A of Wirasakti Atambua State Elementary School, West Atambua District. Writing this Best Practice uses a descriptive method. The achievement of Best Practice activities is 100%. This is because all activities have been carried out and the output obtained is in line with expectations. The use of song media to increase student motivation towards the material taught by the teacher is effective. The results of the implementation of Best Practice that have been implemented are: 1). Learning activities using song media related to the material studied every day are effective. 2). The use of song media in learning really helps students' understanding of the material being taught because it can be sung repeatedly both in class and at home. 3). Based on the learning that has been carried out, differences can be felt between students who carry out learning using song media and using the lecture learning model. 4). The activities that have been designed in the RPP (Teaching Module) can be implemented fully in accordance with what has been planned. The increase in students' understanding of the material being taught can be seen from the achievement of student learning outcomes, through the results of the pre-test and post-test that have been carried out by the teacher, where in the pre-test of the total number of students in class IV A, only 7 students or 2.24% who are able to achieve the KKM value. Meanwhile, in the post test results, there was a significant increase, namely 25 students, 7 students or 2.24% achieved the KKM score and 18 students or 92.8% were able to achieve a score above the KKM score.